Technical efficiency of tea processing units in Iran - Kavoosi-Kalashami Mohammad; Shahnazari Parviz (Ekonomika Poljoprivrede (1979), 2018)
This study used Data Envelopment Analysis (DEA) to measure the technical efficiency of tea processing units in Rudsar County, northern Iran. The required data sets were collected in 2014 by filling out questionnaires and interviewing with the managers of tea processing units. As an innovation, satisfaction level of the main buyer of the produced tea was considered as output in DEA model. Based on the results of CCR input-oriented model, 19% of tea processing units with efficiency score of 1 were identified as efficient units and 81% of units had inefficient performance. The minimum technical efficiency score is equal to 0.479 and the average technical efficiency in these units is equal to 0.727. The results of correlation analysis showed that there was a direct and significant correlation between the time of rolling and the withering temperature with the technical performance of tea processing units.